How host country governments can ensure competitive neutrality in cross-border M&As - Phil Baumann (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2022)
In cross-border M&A transactions, certain investors enjoy government-created, undue competitive advantages. To ensure competitive neutrality, host country governments may implement investment-control measures. However, how can investment controls be imposed without themselves leading to competitive distortions? This Perspective highlights the key elements that governments need to consider in this regard.
Keywords: 330